Youth netizens as global citizens: digital citizenship and global competence among undergraduate students - Cleofas, Jerome Visperas; Labayo, Czarina C. (Frontiers in Communication, 2024)
The digitalization of everyday life among young people exposed them to knowledge and cultures from societies outside their own. Digital citizenship, characterized by online respect and civic engagement, can facilitate students’ positive interactions within the global community and enhance their global competencies, including self-awareness, intercultural communication, and global knowledge. However, empirical studies linking digital citizenship and global competence are limited.. Drawing from an online survey sample of 698 Filipino undergraduate students, this cross-sectional study examines the relationship between digital citizenship and global competence. Findings indicate that online civic engagement and being a working student positively predict all domains of global competence. Online respect positively correlated with intercultural communication. Certain demographic and education-related variables were significant predictors of at least one domain of global competence (p<0.05). The findings underscore the importance of educational institutions fostering online social participation to cultivate globally competent students.